Exploring Resilience: A Virtual Tour of Disaster-Affected Communities through Digital Photo Stories - Annalisa Sonaria Hasibuan; Rezha Destiadi; Andi Supriadi Chan; Alfannisa Annurallah Fajrin (Gondang: Jurnal Seni dan Budaya, 2024)
This study analyzes and explores disaster village tourism and life situation communication, clarifies the form and virtual scenarios, determines building blocks, and suggests sufficient functional requirements to develop virtual tourism scenarios. The questionnaire survey method is direct and effective for identifying questions; the case analysis method surveys the situation of the disaster village tourist attraction; and the theoretical analysis method discusses theories related to Digital Photo Book. The results indicate that tourists are interested in using Digital Photo Book as an information guide. Digital Photo Book's contribution to tourist information is more significant than conventional information, with 77% of tourists believing that the information provided greatly influenced their interest in the future. 70% of respondents stated that the impact of the information provided reached a satisfactory level. Digital Photo Book is more easily accepted and appreciated by tourists and is more suitable to be applied globally in the aspect of tourism, especially in areas with limited access.